Fluffy Bakery / Azeera Lokman and Nur Aqilah Mohamad - Lokman, Azeera; Mohamad, Nur Aqilah (2017)
The bakery provides freshly prepared bakery and pastry products at all times during business operations. Fluffy Bakery is incorporated in the state of Kuala Lumpur. The bakery is owned by two friends, who are equal partners in the company. These partners represent sales, management and finance / administration areas, respectively. Fluffy Bakery offers a wide variety of unusual flavored brownies, cupcake, whoopie pie and pavlova. The bakery provides a fresh batch of cupcakes and bakes scrumptious brownies that also become the signature for the shop. The bakery is also baking at all times during business hours and will also bake to order for orders.